Using Spatial Context and Demographic Analysis to Assess Surface Permeability in Philadelphia - Zhu, Nicholas (Consilience, 2022)
Surface permeability significantly impacts the urban environment. Specifically, impermeable surfaces result in runoff, which in turn causes flooding and pollution. Left unchecked, impermeable surfaces can lead to hazardous conditions for unlucky city residents. These concerns are prominent in Philadelphia, and in response the municipal government has launched an ambitious plan to increase permeability by installing green infrastructure. This paper explores how spatial and demographic research can be combined to provide a holistic assessment of surface permeability across one of America’s largest cities. First, 2020 satellite imagery, provided by the USGS, was used to classify permeable and impermeable surfaces over the entire city. Next, demographic data from the 2014-2018 American Community Survey – household income, rent, and home value, all by census block group – were individually merged with the surface permeability classification to generate three overlays (e.g., surface permeability correlated with household income). Upon quantitative and qualitative examination of these overlays, it was found that impermeable surfaces are unevenly distributed and inequitably concentrated in Philadelphia’s less-affluent communities. Overall, the methodology used in this research demonstrates a multi-disciplinary and reproducible procedure for joint environmental-demographic research. Additionally, the conclusions reached offer location-specific insights that can help inform Philadelphia’s future green infrastructure investments and runoff mitigation strategies.